2020
DOI: 10.3390/sym12020321
|View full text |Cite
|
Sign up to set email alerts
|

Energy of Accelerations Used to Obtain the Motion Equations of a Three- Dimensional Finite Element

Abstract: When analyzing the dynamic behavior of multi-body elastic systems, a commonly used method is the finite element method conjunctively with Lagrange’s equations. The central problem when approaching such a system is determining the equations of motion for a single finite element. The paper presents an alternative method of calculation theses using the Gibbs–Appell (GA) formulation, which requires a smaller number of calculations and, as a result, is easier to apply in practice. For this purpose, the energy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In the rigid kinematics, the orthonormal operator [T] is used to change the components of a vector from the mobile reference frame to the fixed one (global), {t} G = [T]{t} L . Differentiating the matrix [T], it obtains the angular velocity and operator/vector andthe angular acceleration operator/vector ( [20]).…”
Section: Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rigid kinematics, the orthonormal operator [T] is used to change the components of a vector from the mobile reference frame to the fixed one (global), {t} G = [T]{t} L . Differentiating the matrix [T], it obtains the angular velocity and operator/vector andthe angular acceleration operator/vector ( [20]).…”
Section: Kinematicsmentioning
confidence: 99%
“…We note that we have to make three differentiations {∂L/∂ḋ}, (d/dt){∂L/∂ḋ}, {∂L/∂d} whereas in the case of applying the Gibbs-Appell equations it is only necessary to make a single differentiation {∂E a /∂d} [20]. This can reduce the computation time and thus an advantage when applying FEA to MBS with elastic elements.…”
Section: Lagrange's Equationsmentioning
confidence: 99%
“…where q is the vector of independent coordinates of the whole system. Introducing (28) in (27), it obtains:…”
Section: ∆ + [C]mentioning
confidence: 99%
“…The analytical methods of studying MBS and the possibilities of obtaining these equations are presented in [22][23][24][25]. The Gibbs-Appell method is a method rarely found in studies, but it may be of interest to researchers to use this method in analyzing MBS systems with elastic elements [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…For nonholonomic systems, Kane's equations can also be used, and it seems that in the last decade, their use has begun to be applied to problems that require the dynamic analysis of complex systems. The latest research on applying the method to MBS systems with elastic elements can be found in [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%